Modelos de contrarreação cosmológica. - Barbosa, Rodrigo Martins de Siqueira (2016)
The standard cosmological picture requires, to explain properly the observable data, energy components that are very unusual compared to the ones we are familiar within the standard model of particles; these are known as ”Dark Energy”and ”Dark Matter”. Even though they are well accepted, their origins are still controversial. One proposal to explain such concepts is the backreaction caused by the inhomogeneity in the matter distribution of the universe. In this work we present the Buchert’s backreaction formalism, and we use it to show that a viscous pression can be understood as a consequence of backreaction. Later, we establish an average model based on an LTB solution, linearized with respect to the curvature parameter. We then compare against the data using a ”template”metric that allows us to relate the redshift in this model to a close realization to the usual formalism.